2007
DOI: 10.1007/s00253-006-0765-z
|View full text |Cite
|
Sign up to set email alerts
|

Codon optimization of Bacillus licheniformis β-1,3-1,4-glucanase gene and its expression in Pichia pastoris

Abstract: Beta-1,3-1,4-glucanase (EC3.2.1.73) as an important industrial enzyme has been widely used in the brewing and animal feed additive industry. To improve expression efficiency of recombinant beta-1,3-1,4-glucanase from Bacillus licheniformis EGW039(CGMCC 0635) in methylotrophic yeast Pichia pastoris GS115, the DNA sequence encoding beta-1,3-1,4-glucanase was designed and synthesized based on the codon bias of P. pastoris, the codons encoding 96 amino acids were optimized, in which a total of 102 nucleotides were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 42 publications
4
43
0
Order By: Relevance
“…To obtain high-purity and high-yield expression of secreted CysC protein, we chose the pPIC9K expression vector and the P. pastoris GS115 strain as the host to express CysC, since a number of studies have concluded that many proteins produced in P. pastoris are similar in structure and bioactivity to the native proteins produced in mammalian cells (Ouchkourov et al, 2002;Hu et al, 2006;Teng et al, 2007;Fu et al, 2011;Huang et al, 2012;Yang et al, 2012). Moreover, the pPIC9K vector has an α-factor secretion signal sequence, which has been used with great success.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain high-purity and high-yield expression of secreted CysC protein, we chose the pPIC9K expression vector and the P. pastoris GS115 strain as the host to express CysC, since a number of studies have concluded that many proteins produced in P. pastoris are similar in structure and bioactivity to the native proteins produced in mammalian cells (Ouchkourov et al, 2002;Hu et al, 2006;Teng et al, 2007;Fu et al, 2011;Huang et al, 2012;Yang et al, 2012). Moreover, the pPIC9K vector has an α-factor secretion signal sequence, which has been used with great success.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have been carried out to improve its activity and performance by DNA recombinant techniques (Chen et al, 2001;Teng et al, 2007;Li et al, 2009). However, little attention has been paid to the practicability and safety of the application of β-1,3-1,4-glucanase in the food industry.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, β-1,3-1,4-glucanase is made by separation and purification from natural sources, such as Penicillium emersonii, Aspergillus niger, Bacillus subtilis, and Trichoderma reesei (Harman and Kubicek, 1998).microorganisms, including Lactococcus lactis , Escherichia coli (Teng et al, 2006;Qiao et al, 2009), Pichia pastoris (Teng et al, 2007), and Saccharomyces cerevisiae (Hinchliffe and Box, 1984;van Rensburg et al, 1997;Zhang Q. et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The yield of the recombinant β-glucanase was higher than those by previous studies. A β-1,3-1,4-glucanase from Bacillus licheniformis was expressed with a yield of 256.7 U/mL in P. pastoris (Teng et al 2007) and a truncated β-1,3-1,4-glucanase from Fibrobacter succinogenes was produced with a yield of 1,940 U/mL in P. pastoris (Wen et al 2005). The characterization of the recombinant β-1,3-1,4-glucanase was studied in a detail.…”
Section: Characterization Of the Recombinant β-13-14-glucanasementioning
confidence: 99%